Asksia AI LOGO

Sia

olivia131311's Question
Math
Posted 3 months ago

CBC Kunming - No. 10 Senior High School
Kunming, Yunnan
12. Rationaliz the given radical expression. Show your complete work.
Canama Datisis Columbia
a. 573\frac{-\sqrt{5}}{\sqrt{7}-3}
b. 53+232\frac{5 \sqrt{3}+\sqrt{2}}{\sqrt{3}-\sqrt{2}}
[2]
13. Determine whether the given value of x is a root of the equation.
[2]
a. 2x+1=9x;x=16\sqrt{2 x+1}=9 x ; x=16
b. 3x6=6;x=14\sqrt{3 x-6}=6 ; x=14
14. Which of these equations have real roots? Justify your answers.
[4]
a. 2x+B=33x+12 \sqrt{x+B}=3 \sqrt{3 x+1}
b. 2x8=33x+12 \sqrt{x-8}=3 \sqrt{3 x+1}
15. Solve the value of xx and check if there is extraneous roots.
[3]
x+3=3x2
\sqrt{x+3}-=\sqrt{3 x-2}
Sign in to unlock the answer
Answer from Sia
Posted 3 months ago
Solution by Steps
step 1
To rationalize the expression fracsqrt5sqrt73\\frac{-\\sqrt{5}}{\\sqrt{7}-3}, we multiply the numerator and denominator by the conjugate of the denominator, which is sqrt7+3\\sqrt{7}+3
step 2
This gives us fracsqrt5(sqrt7+3)(sqrt73)(sqrt7+3)\\frac{-\\sqrt{5} (\\sqrt{7}+3)}{(\\sqrt{7}-3)(\\sqrt{7}+3)}. The denominator simplifies to 79=27 - 9 = -2
step 3
Therefore, we have fracsqrt5(sqrt7+3)2=fracsqrt5(sqrt7+3)2\\frac{-\\sqrt{5} (\\sqrt{7}+3)}{-2} = \\frac{\\sqrt{5} (\\sqrt{7}+3)}{2}
step 4
This can be further simplified to frac3sqrt52+fracsqrt352\\frac{3\\sqrt{5}}{2} + \\frac{\\sqrt{35}}{2}
step 5
The final result is frac3sqrt5+sqrt352\\frac{3\\sqrt{5} + \\sqrt{35}}{2}
step 6
Now, for the second expression frac5sqrt3+sqrt2sqrt3sqrt2\\frac{5\\sqrt{3} + \\sqrt{2}}{\\sqrt{3}-\\sqrt{2}}, we again multiply by the conjugate sqrt3+sqrt2\\sqrt{3} + \\sqrt{2}
step 7
This results in frac(5sqrt3+sqrt2)(sqrt3+sqrt2)(sqrt3sqrt2)(sqrt3+sqrt2)\\frac{(5\\sqrt{3} + \\sqrt{2})(\\sqrt{3} + \\sqrt{2})}{(\\sqrt{3}-\\sqrt{2})(\\sqrt{3}+\\sqrt{2})}. The denominator simplifies to 32=13 - 2 = 1
step 8
The numerator expands to 5cdot3+5sqrt6+sqrt6+2=17+6sqrt65\\cdot3 + 5\\sqrt{6} + \\sqrt{6} + 2 = 17 + 6\\sqrt{6}
step 9
Thus, the final result is 17+6sqrt617 + 6\\sqrt{6}
Answer
The rationalized forms are frac3sqrt5+sqrt352\\frac{3\\sqrt{5} + \\sqrt{35}}{2} and 17+6sqrt617 + 6\\sqrt{6}.
Key Concept
Rationalizing expressions involves eliminating radicals from the denominator by multiplying by the conjugate.
Explanation
The process of rationalization simplifies the expressions, making them easier to work with in further calculations.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question